Future Horizons: AI-Enhanced Threat Detection in Cloud Environments: Unveiling Opportunities for Research - Haroon Arif; Aashesh Kumar; Muhammad Fahad; Hafiz Khawar Hussain (International Journal of Multidisciplinary Sciences and Arts, 2024)
In this extensive and comprehensive review paper, we delve into the dynamic landscape of artificial intelligence (AI)-enhanced threat detection within cloud environments. The evolution of this field, from traditional methodologies to the seamless integration of AI, is meticulously explored, providing a nuanced understanding of the transformative potential of AI in bolstering cyber security measures. The exploration encompasses a myriad of crucial aspects, offering readers a holistic view of the subject. The revolutionary impact of AI is scrutinized, emphasizing its role in reshaping the conventional paradigms of threat detection and response. The paper meticulously addresses current challenges in cloud security, providing insights into the multifaceted nature of contemporary threats and how AI serves as a robust defense mechanism. As we navigate through the intricacies of this field, the review paper sheds light on ongoing research prospects, presenting a roadmap for future endeavors. Real-world case studies are examined to illustrate the practical applications of AI-enhanced threat detection, offering valuable lessons and perspectives for decision-makers, researchers, and practitioners in the realm of cyber security. Ethical considerations are given due attention, as the integration of AI in threat detection raises important questions surrounding privacy, bias, and accountability. By analyzing current trajectories and emerging technologies, the article provides readers with a forward-looking perspective, helping them anticipate the evolving landscape of cyber security. In addition to exploring the technological facets, the paper emphasizes the importance of a collaborative approach and ongoing adaptation. The interconnected nature of threats in the digital realm necessitates a collective effort from industry experts, researchers, and policymakers. The review paper advocates for a holistic strategy that integrates AI technologies with human expertise to create a resilient defense against the ever-evolving landscape of cyber threats.